Aging of European power plant infrastructure as an opportunity to evolve towards sustainability. (13th July 2017) - Farfan, Javier; Breyer, Christian
Abstract: The global energy sector is shifting towards renewable energy (RE). When it comes to RE, Europe is the leading region for renewable share installation with 38.5% of RE of total power capacity (including 15% new RE), but still there were 914 GW of non-RE installed capacities operating at end of 2014. Records of decommissioned power plants indicate an average power plant technical lifetime of about 40 years for coal, 34 years for gas and 34 years for oil power plants. An assumed lifetime for nuclear power plants is 40 years, and the average age of the operating nuclear power stations is 30 years. From numbers related to non-RE capacities operating at end of 2014 and following this tendency, only 340 GW would still be operational by 2030, which implies the shutdown of 48.6% of the gas, 78.3% of the oil, 79.1% of the coal and 81.7% of the nuclear capacities. By 2050 only 6.1% and 1.4% of the currently operating capacity will be within the lifetime range for coal and nuclear, respectively, while 100% of the currently operating capacities of gas and oil would have reached the expected lifetime. From the total of the fossil and nuclear capacities of Europe, 65% is operating within the European Union, 72.3% of which is in Germany, France, Spain, Italy, United Kingdom and the Nordics. This presents a prime opportunity for Europe to evolve and set the example on the way towards sustainable power systems. To achieve the target of limiting climate change to 2 °C, net zero greenhouse gas emissions by 2050 may be required, resulting in 17 GW of coal capacities installed in Europe from 2010 onwards facing a shorter-than-expected operational lifetime, which will lead to stranded assets. Gas and oil-fired capacities commissioned from 2016 onwards may be required to shift to carbon-neutral fuels such as biodiesel or RE-based syngas. Highlights: The European power sector experience constant growth and continuous evolution. Renewable Energy installations in Europe have steadily increased since the 1990s. European Nuclear and Coal installations have been in decline since the 1980s. Fossil capacities are expected to have a sharp decommissioning rate by 2024. Germany, UK, France, Italy, Spain and Nordics should lead a sustainable transition.